2023
DOI: 10.3390/ma16031286
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Improved POA-RF Model in Predicting the Strength and Energy Absorption Property of a Novel Aseismic Rubber-Concrete Material

Abstract: The application of aseismic materials in foundation engineering structures is an inevitable trend and research hotspot of earthquake resistance, especially in tunnel engineering. In this study, the pelican optimization algorithm (POA) is improved using the Latin hypercube sampling (LHS) method and the Chaotic mapping (CM) method to optimize the random forest (RF) model for predicting the aseismic performance of a novel aseismic rubber-concrete material. Seventy uniaxial compression tests and seventy impact tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The error functions were employed to evaluate the fit of the isotherm to the experimental equilibrium data. In this study, the residual root mean square error ( RMSE —Equation (9)), the chi-square test (Equation (10)) and the linear regression were used [ 36 , 37 ]: where n is the number of observations in the experimental isotherm, and q e,exp and q e,cal stand for experimental and calculated values, respectively. The better the curve fitting, the smaller the RMSE and χ 2 values.…”
Section: Methodsmentioning
confidence: 99%
“…The error functions were employed to evaluate the fit of the isotherm to the experimental equilibrium data. In this study, the residual root mean square error ( RMSE —Equation (9)), the chi-square test (Equation (10)) and the linear regression were used [ 36 , 37 ]: where n is the number of observations in the experimental isotherm, and q e,exp and q e,cal stand for experimental and calculated values, respectively. The better the curve fitting, the smaller the RMSE and χ 2 values.…”
Section: Methodsmentioning
confidence: 99%
“…Wanhui Feng et al [32] investigated the dynamic fracture toughness of RC using the drop weight test, which showed that the fracture toughness of RC increased to 30% at the time of the increase in rubber content. In the rest of the studies, the RC also showed excellent thermal insulation [33] and energy absorption properties [20,34].…”
Section: Introductionmentioning
confidence: 93%
“…The authors [73] proposed Pelican Optimization Algorithm (POA) that tries to imitate the behavior of pelicans during hunting. Some recent applications of COA in optimization problems are described in [109][110][111][112][113][114]. The positions of the pelican will be the variables of this problem of searching for the optimal value of the objective function.…”
Section: Pelican Optimization Algorithm (Poa)mentioning
confidence: 99%